Scoping Review: Efek Pegagan (Centella asiatica) dalam Sediaan Topikal terhadap Pencegahan Penuaan Dini - Novita Arya Cahyani; Herri S. Sastramihardja; Siska Nia Irasanti (UNISBA Press, 2022)
Abstract. One of the problems that are often encountered today in the practice of dermatologists and genital specialists is premature aging. Natural products have proven to be the best choice for preventing premature aging due to environmental concerns, safety from synthetic chemicals, and health. One of these natural products is pegagan (C. asiatica). There have been many studies showing the benefits of pegagan, especially its content that is able to stimulate collagen synthesis in skin fibroblast cultures. However, research dataregarding the effectiveness of pegagan on anti-aging is still very limited. The purpose of this study was to determine the effect of pegaganin topical preparations on the prevention of premature aging. The research was conducted using the method of scoping review with samples of national and international scientific articles that meet the eligibility criteria (eligible). The results of this study were taken from three databases, namely Proquest, ScienceDirect, and Google Scholar, with an initial search result of 4.173. There were 1,536 articles according to the inclusion criteria, and the exclusion criteria and PICOS were four articles and the results of the feasibility test based on a critical study were also four articles. The results of the four articles that have been analyzed stated that the group that was given pegagan extract topically showed an antiaging effect more than the control group. The conclusions of the research suggest that pegagan in topical preparations, either managed with HA, glycerine, chitosan nanoparticles, or extracted Camellia sinensis and Glycine max has a role in preventing premature aging. Abstrak. Salah satu masalah yang sering dijumpai saat ini dalam praktik dokter spesialis kulit dan kelamin adalah penuaan dini. Produk alami telah terbukti menjadi pilihan yang terbaik untuk mencegah penuaan dini karena pertimbangan dari kesadaran lingkungan, keamanan dari bahan kimia sintesis, dan kesehatan. Salah satu produk alami tersebut adalah pegagan (C. asiatica). Telah banyak penelitian yang menunjukkan manfaat pegagan terutama kandungannya yang mampu merangsang sintesis kolagen dalam kultur fibroblas kulit. Namun data penelitian terkait efektivitas pegagan terhadap anti-aging masih sangat terbatas. Tujuan penelitian ini adalah untuk mengetahui efek pegagan dalam sediaan topikal terhadap pencegahan penuaan dini. Penelitian diambil dengan metode scoping review dengan sampel artikel ilmiah nasional dan internasional yang memenuhi kriteria kelayakan (eligible). Hasil dari penelitian ini diambil dari tiga database yaitu Proquest, ScienceDirect, dan Google Scholar dengan hasil pencarian awal terdapat 4.173. Artikel yang sesuai kriteria inklusi sebanyak 1.536, dan kriteria eksklusi beserta PICOS terdapat empat artikel dan hasil uji kelayakan berdasarkan telaah kritis tersisa sebanyak empat artikel. Hasil dari keempat artikel yang telah dianalisis, menyatakan bahwa kelompok yang diberikan intervensi ekstrak pegagan secara topikal menunjukkan adanya efek anti-aging daripada kelompok kontrol. Simpulan dari penelitian adalah pegagan dalam sediaan topikal baik pengelolaannya dengan HA, glycerine, nanopartikel kitosan, atau ekstrak Camellia sinesis dan Glycine max, memiliki peran dalam mencegah penuaan dini.